Physiological profile of elite junior badminton players in South Africa - Lieshout, Kerry Ann van (2008)
M.Phil. === There is a lack of descriptive data on the physiological and physical profiles of elite junior badminton players in South Africa. The purpose of this study was to measure and describe the body composition, aerobic power, muscular characteristics, speed, flexibility and agility of the elite junior badminton players in South Africa. Eight male and seven female badminton players between the ages of 14 and 18 years who were selected for the junior national badminton squad of South Africa participated in this study. The players participated in the following field tests: multistage-shuttle run; vertical jump; lunge jump; sit-ups; push-ups; forwards and backwards speed at 2,4, and 6m and the SEMO agility test. Each subject was tested on the Cybex II Isokinetic Dynamometer to determine absolute and relative peak torque of the hamstring and quadriceps muscle groups, the functional and conventional hamstring:quadriceps ratios, as well as the arm power-endurance ratios. Flexibility was measured using the Leighton Flexometer. The following means (+ SD) were observed for the male players: height 180.4 (8.1)cm; mass 73.4 (9.7)kg; body fat 9.6 (1.6)%; somatotype 3.0:4.1:3.1 (1.0:1.1:1.0) and VO2max 50.7 (3.0) mlO2.kg-1.min-1. The female players had the following means (+ SD): height 161.2 (4.3)cm; mass 58.1 (7.9)kg; body fat 19.2 (4.5)%; somatotype 4.0:4.3:2.0 (1.0:1.1:0.7) and VO2max 42.0 (2.8) mlO2.kg-1.min-1. The physical fitness components of the players in this study that were found to be weaker than the norm, and would need to be improved greatly included their aerobic power, leg power and flexibility. Other fitness areas that were not necessarily found to be a weakness, but could be improved further to enhance their game, is their hamstring strength, eccentric leg strength, upper body and abdominal endurance, backward speed and agility. === Mr. A.J.J. Lombard